Liujunzi decoction attenuates cisplatin-induced anorexia in rats via inhibiting PERK/eIF2α/ATF4/CHOP pathway and GDF15/GFRAL expression - Yongzhao Dai; Wanting Hu; Jinyuan Han; Yaozhong Zhao; Xipei Wu; Xiuxiu Liao; Ke Nie (KeAi Communications Co., Ltd., 2024)
Background and aim: Liujunzi Decoction (LJZD), also called Rikkunshito, is a traditional formula that has proven effective in clinical treatment against chemotherapy-induced anorexia (CIA). Previous study indicated the importance of GDF15/GFRAL axis in the pathogenesis of CIA, and suggested the potential connection between endoplasmic reticulum stress and GDF15 expression. However, further exploration is required to determine whether the mechanism of LJZD against CIA is related to the PERK/eIF2α/ATF4/CHOP signaling and GDF15/GFRAL expression. Methods: The CIA model of rats was established via intraperitoneal injection of cisplatin, and the rats were given LJZD orally for 72 ​h. Food intake and body weight were recorded daily. The expression of GDF15/GFRAL and ER stress factors, as well as the histological injuries were investigated. Results: LJZD led to a significant increase in food intake in rats and a decrease in serum GDF15 levels at 24 ​h and 72 ​h after cisplatin injection. This effect may be associated with the inhibition of Gdf15 transcription and the amelioration of pathological injuries or endoplasmic reticulum stress in the liver and ileum. Moreover, LJZD suppressed the cisplatin-induced activation of the hepatic and ileal PERK/eIF2α/ATF4/CHOP pathway, resulting in the alleviation of central GDF15/GFRAL expression. Conclusion: LJZD effectively improves cisplatin-induced anorexia in a rat model, which might be attributed to its inhibition of the PERK/eIF2α/ATF4/CHOP pathway and GDF15/GFRAL expression activated by cisplatin.